2022
DOI: 10.4149/bll_2022_032
|View full text |Cite
|
Sign up to set email alerts
|

National study on use of artificial intelligence in breast disease and cancer

Abstract: BACKGROUND: The aim of this study was to examine the thoughts, reservations, approaches and perspectives on the future of artifi cial intelligence (AI) held by physicians specializing in breast healthcare in our country. METHODS: Our survey was sent to the members of the Federation of Turkish Breast Disease Associations (MHDF) by e-mail. The survey investigates the attitudes towards the use of AI in breast disease and cancer, including demographic characteristics of the participants, their daily practice and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…With regard to accuracy, in cardiovascular field, Chung et al ( 8 ) report that “the use of AI-ECG algorithms for rhythm identification and ECG interpretation can be more accurate in interpretation” than current ECG software, and also affirm that AI-based ECG analysis has been proposed as an accurate screening tool in valvular disease field. In breast disease and cancer care area, the use of AI is thought to lead to rapid diagnosis and more detailed evaluation ( 9 ). It is important to note, with regard to computer-aided detection (CAD) software that, according to Mezrich ( 10 , 11 ), these can increase radiologists’ accuracy and fastness, but they act as a “second set of eyes.” Consistently, Vedantham et al ( 12 ) affirm that it is more likely that AI will be used as a second reader, and Harvey and Gowda ( 13 ) reports the greater effectiveness of algorithms when subject to human oversight.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to accuracy, in cardiovascular field, Chung et al ( 8 ) report that “the use of AI-ECG algorithms for rhythm identification and ECG interpretation can be more accurate in interpretation” than current ECG software, and also affirm that AI-based ECG analysis has been proposed as an accurate screening tool in valvular disease field. In breast disease and cancer care area, the use of AI is thought to lead to rapid diagnosis and more detailed evaluation ( 9 ). It is important to note, with regard to computer-aided detection (CAD) software that, according to Mezrich ( 10 , 11 ), these can increase radiologists’ accuracy and fastness, but they act as a “second set of eyes.” Consistently, Vedantham et al ( 12 ) affirm that it is more likely that AI will be used as a second reader, and Harvey and Gowda ( 13 ) reports the greater effectiveness of algorithms when subject to human oversight.…”
Section: Resultsmentioning
confidence: 99%
“…The topic of time emerges also from the surveys of Pecqueux et al ( 16 ), in terms of reduction of time spent by specialists on monotonous tasks, and of Emiroglu et al ( 9 ), in terms of possibility to get to a rapid diagnosis and to examine a larger number of patients. Moreover, AI may filter out non-complex cases letting a greater focus of specialists on more challenging cases ( 18 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted with radiologists and radiographers, it is seen that there is a lack of knowledge about artificial intelligence [ 32 ]. In a study on the use of artificial intelligence in breast diseases, it was seen that the majority of participating physicians had insufficient knowledge about artificial intelligence [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study by Emiroglu and colleagues, which examined the thoughts, reservations, approaches, and perspectives of specialized physicians in breast health in our country regarding the future of AI, showed that the use of AI technology in the diagnosis and treatment of breast cancer is beneficial for both physicians and patients. However, it revealed that physicians have also concerns about potential medical errors and liability issues that AI may cause (19). Participants who expressed that they are not afraid of AI and robots have relegated such concerns to a secondary position and have not given them importance.…”
Section: Discussionmentioning
confidence: 99%